Brain network segregation attenuates tau spreading in Alzheimer's disease. (20th December 2022) - Steward, Anna; Biel, Davina; Luan, Ying; Brendel, Matthias; Dewenter, Anna; Roemer, Sebastian Niclas; Rubinski, Anna; Dichgans, Martin; Ewers, Michael; Franzmeier, Nicolai
Abstract: Background: In Alzheimer's disease (AD), the functional connectome plays a key role in the trans‐neuronal spreading of tau pathology, a key driver of cognitive decline. The functional connectome is comprised of segregated, but communicating networks which lose segregation with age, resulting in an overall more diffuse connectome. Prior neuroimaging studies have found an association between weaker network segregation and faster symptom manifestation in AD, however, it is unclear if this association occurs because of a more diffuse connectome facilitating connectivity‐mediated tau spreading. Method: To investigate if network segregation is linked with accelerated tau spreading, we combined resting‐state fMRI with longitudinal Flortaucipir tau‐PET in 36 healthy controls and 57 biomarker‐defined AD subjects spanning the preclinical to dementia spectrum. Network segregation (the between to within‐network connectivity balance) was estimated at the subject level with resting‐state‐fMRI‐determined connectivity between 400 cortical regions of interest belonging to seven major networks. Result: Results revealed that higher baseline entorhinal tau‐PET (Braak I) was associated with accelerated tau accumulation in the rest of the brain (Braak III‐VI) in the AD and pooled sample, yet subjects with stronger network segregation exhibited an attenuated effect (Fig.1A). Additionally, through modelling patient‐specific tau epicentres we similarly demonstrated that subjects with high epicentre segregation exhibited an attenuated tau accumulation rate in the remaining brain (Fig1B). Conclusion: In line with the concept that tau spreads trans‐neuronally, our findings suggest that a more diffuse network topology facilitates tau expansion and further emphasises the critical role of the functional connectome in routing the spread of tau.